2015
DOI: 10.7567/jjap.54.10nd06
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-energy-harvesting properties of hydrothermally synthesized (K,Na)NbO3films deposited on flexible metal foil substrates

Abstract: Energy-harvesting properties were investigated for the flexible piezoelectric devices, Pt/hydrothermally synthesized (K 0.88 Na 0.12 )NbO 3 /SrRuO 3 / metal foil, fabricated at low process temperatures below 300 °C. Fabricated devices had high flexibility, and cracking and peeling were not observed under the bending condition with the maximum curvature of 5.2 mm. The estimated Young's modulus of the fabricated flexible devices was 37 GPa. The pulse poling treatment with AC voltage above 150 V enhanced the ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…We compared our energy-harvesting performance with those of other reported piezoelectric thin-film-based cantilever harvesters, as shown in Figure . , All relevant values, including voltage, power, and power density, are listed in the accompanying table. Extended plots of the comparative energy-harvesting performance are demonstrated in Figure S10 with more information in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…We compared our energy-harvesting performance with those of other reported piezoelectric thin-film-based cantilever harvesters, as shown in Figure . , All relevant values, including voltage, power, and power density, are listed in the accompanying table. Extended plots of the comparative energy-harvesting performance are demonstrated in Figure S10 with more information in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, it was found that K-rich (K,Na)-NbO 3 films (sodium content: between 1020 %) deposited by the hydrothermal method exhibited dielectric and piezoelectric properties suitable for applications to sensors and energy harvesters. 25) It was also shown that the piezoelectric property can be improved by Ta substitution. 26) Therefore, it is expected that the morphological control of the hydrothermally-synthesized (K,Na)(Nb,Ta)O 3 powders with K-rich composition lead to achieve the highperformance devices.…”
Section: Introductionmentioning
confidence: 99%
“…Their power density was relatively high value in an ambient frequency among lead-free piezoelectric films. 23) To increase power generation i.e. act as energy harvesters, the thicker films are required because the generated power is proportional to the film thickness.…”
Section: Introductionmentioning
confidence: 99%